What Are the Interoperability Requirements for Clinical AI? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2019)
Artificial intelligence (AI) is poised to revolutionize healthcare, offering the potential to improve diagnostics, personalize treatments, and streamline cli...
Keywords: AI in Clinical Decision Support; Interoperability; Requirements; Clinical; Artificial Intelligence; Machine Learning; Healthcare